2020
DOI: 10.1016/j.jsams.2020.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Concussion knowledge, attitudes and behaviour in equestrian athletes

Abstract: Objective: To determine knowledge, attitudes and behaviour towards concussion in adult equestrian athletes. Design: Nationwide, cross-sectional, questionnaire. Methods: Participants were recruited via advertisements circulated through social media, community presentations and equestrian organisations. Participants were sent a web link to an online questionnaire previously designed for high school athletes and modified to ensure relevance to equestrian activities. The percentage of correct responses per item an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
3
4
1
Order By: Relevance
“…There is no significant difference in the impact of sports behavior on different genders after using multi-media teaching to intervene in the physical education curriculum, which means that the performance of students' sports behavior will not be different because of gender. This result differs from most scholars' results (17,18). According to the research results, multi-media teaching applied to indoor physical education courses can improve students' sports performance without being restricted by gender.…”
Section: Discussioncontrasting
confidence: 97%
“…There is no significant difference in the impact of sports behavior on different genders after using multi-media teaching to intervene in the physical education curriculum, which means that the performance of students' sports behavior will not be different because of gender. This result differs from most scholars' results (17,18). According to the research results, multi-media teaching applied to indoor physical education courses can improve students' sports performance without being restricted by gender.…”
Section: Discussioncontrasting
confidence: 97%
“…Fortunately, the majority of our respondents correctly identified many of the more common concussion symptoms. Our results are in agreement with a similar study done among New Zealand equestrians [12] with similar rates being reported in motocross participants [21] and soccer players [22].…”
Section: Discussionsupporting
confidence: 93%
“…Despite these advancements, even the best technology does not work if helmets are not worn, are stored in improper conditions or are not replaced after a potentially damaging blow. Our results also indicate that equestrians need better education to know how to store, clean and replace helmets frequently, and are in agreement with other work in this area [12]. Those riders who do wear helmets on a regular basis to protect themselves but do not follow helmet care guidelines leave themselves more vulnerable to injury than they may perceive.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Females had higher levels of concussion knowledge than males. The reasons for this difference remain unclear but mirror findings from other sports such as equestrian activities (35). Further exploration of the role of these factors on concussion knowledge in different sports may be beneficial to help identify the audiences who may benefit most from being targeted with further education.…”
Section: Total Concussion Knowledge Scoresmentioning
confidence: 90%